2015
DOI: 10.7202/1033189ar
|View full text |Cite
|
Sign up to set email alerts
|

Accès aux services sociaux et de santé en français : l’expérience des Franco-Manitobains

Abstract: Des progrès considérables sont constatés dans l’offre de services et la formation de professionnels dans le domaine des services sociaux et de santé en français au Manitoba depuis les 30 dernières années. L’objectif de cette recherche est de mieux connaître la perception des usagers quant aux services couramment disponibles et aux barrières réduisant l’accès à ces services. L’obtention de services en français est importante pour la population francophone, particulièrement pour les aînés et les immigrants. En m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
0
12
0
4
Order By: Relevance
“…Recruitment, training, and retention of professionals fluent in French have also been promoted as the primary strategy to increase provision of French language services (FLSs) (52,53). Shortage of bilingual health professionals (44,53), however, results in inconsistency or unavailability of language concordant services. To facilitate access to FLSs, providers are encouraged to practice active offer (54).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment, training, and retention of professionals fluent in French have also been promoted as the primary strategy to increase provision of French language services (FLSs) (52,53). Shortage of bilingual health professionals (44,53), however, results in inconsistency or unavailability of language concordant services. To facilitate access to FLSs, providers are encouraged to practice active offer (54).…”
Section: Introductionmentioning
confidence: 99%
“…The official minority language (OML) speakers in these regions are Francophones; they represent 3.8% of the population, although this percentage reaches 32% in 1 province (New Brunswick); it is consistently lower in other provinces and territories (42). Studies have shown that minority Francophones are at greater risk of poor health (43) and have poorer access to health care (43 45).…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, efforts to promote recruitment, training, and retention of professionals fluent in French have been promoted as the primary strategy to increase provision of French language services (FLS). 14,15 Shortage of bilingual health professionals, 16,17 however, means that language concordant services are not consistently available. To facilitate access to FLS, providers are encouraged to practice active offer (note 1).…”
Section: Introductionmentioning
confidence: 99%
“…Findings relative to barriers to FLS delivery are consistent with previous research. [18][19][20] Financial constraints, shortage of bilingual staff, and limited resources for translation and interpretation services are significant barriers. Distinct strategies are needed to recruit bilingual healthcare providers 20 and train interpreters 38 in official language minority communities.…”
Section: Discussionmentioning
confidence: 99%
“…Active offer is defined as a range of health services available in French and offered proactively; they are clearly announced, visible, and easily accessible at all times (note 1). Providing FLS in linguistic minority communities is challenging, with shortage of bilingual staff, poor identification of Francophone clients and professionals, limited support to practice active offer, 18,19 and few recruitment and retention strategies aimed specifically at bilingual personnel. 20 Furthermore, even in cases of FLS availability, fragmentation in linguistic continuity of care is reported when several service providers participate in service delivery.…”
Section: Introductionmentioning
confidence: 99%